2015
DOI: 10.1039/c5nr04772b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and optimising the packing density of perylene bisimide layers on CVD-grown graphene

Abstract: ABSTRACT:The non-covalent functionalization of graphene is an attractive strategy to alter the surface chemistry of graphene without damaging its superior electrical and mechanical properties. Using the facile method of aqueous-phase functionalization on large-scale CVDgrown graphene, we investigated the formation of different packing densities in self-assembled monolayers (SAMs) of perylene bisimide derivatives and related this to the amount of substrate contamination. We were able to directly observe wet-che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…16 More specifically, we found that graphene with polymer residues from the transfer process produces a lower packing density molecular layer than that of graphene that has been annealed to remove these residues, similar to what has been described by other groups. 17,18 In this communication,…”
supporting
confidence: 69%
See 3 more Smart Citations
“…16 More specifically, we found that graphene with polymer residues from the transfer process produces a lower packing density molecular layer than that of graphene that has been annealed to remove these residues, similar to what has been described by other groups. 17,18 In this communication,…”
supporting
confidence: 69%
“…Despite a large error margin, the overall significantly increased intensity of amine and amide components after annealing indicates that the EDA has at least partially successfully coupled with the -COOH groups on the 1 ''anchor''-molecule. Due to the perpendicular orientation of the molecules on the graphene, 16 we do not expect full coupling to occur as at least one -COOH group will be obscured by the presence of those above. In order to further verify the presence of amine end-groups on the graphene surface, the adhesion of bacteria was tested using fluorescence microscopy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As recently reported by Duesberg and co‐workers, the ratio between the ν Ag (ca. 1351 cm −1 ) and the G peak of the graphene substrate can be efficiently used as an estimation of the packing density . Indeed, both isomers exhibited very homogeneous mean PDI ν Ag /G ratios of 1.03 and 0.93 (full width at half maximum (FWHM)=0.10 and 0.11) for the C 3 h and C s isomers, respectively, indicative of a high packing density (Figure b).…”
Section: Resultsmentioning
confidence: 99%